DISINFECTAN STERILIZATION ROOM TO PREVENT MICROCONTROLLER BASED COVID-19 - Vidy Vidy; Muhammad Safii (Multica Science and Technology, 2022)
Microcontroller-based Disinfectant Room is a tool that functions for self-sterilization from the Covid-19 virus. This covid-19 outbreak has been rampant in Indonesia since the end of 2019, to prevent the spread of the covid-19 virus in every region in Indonesia, check the temperature, wash hands, and spraying disinfectant liquid. There are still many areas that still use manual spraying of disinfectant liquid, so a tool is needed that aims to facilitate the automatic self-sterilization process. This tool aims to create a disinfectant chamber tool that uses an ultrasonic sensor as an object detector and an Arduino Uno as a controller. The output used in this study is a relay module that is connected to a 12V DC water pump that will spray disinfectant liquid through a mist nozzle. This tool is effective in detecting objects with a distance of 80 cm – 170 cm in front of the sensor.